IMPROVING STUDENTS’ ENGLISH SPEAKING ABILITY THROUGH JIGSAW - Ubaedillah, Ubaedillah (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
ABSTRACT The aim of this research is to find out the improvement of students? speaking ability through Jigsaw method of the Management Study Program students of the second semester in the academic year 2018/2019 at Muhadi Setiabudi University taught by and without using Jigsaw. The data of the current study were gathered at multiple points of time before and after the end of the experiment to determine the improvement of student?s speking ability through Jigsaw speaking skills. In practical terms, the sample?s speaking ability were first examined through an English oral test prior to and after some Jigsaw instructional activities were provided. The data were analyzed using basic and inferential statistical methods including mean scores, standard deviations, paired sample t-test, and effect size. The findings showed a remarkable development in the students? speaking skills through Jigsaw method. The writer holds an experimental research to apply Jigsaw in teaching English speaking. The population is the second semester students of Muhadi Setiabudi University in the academic year 2018/2019 and the sample are two groups of students placed in experiment and control groups. Using oral test as the instrument, the writer collected the data of the students? speaking ability. The report of the research concludes that Jigsaw improved the English speaking ability of the second semester students in the academic year 2018/2019. By doing small discussion of Jigsaw method it can motivate to develop the student?s braveries to use their knowledge and their experience to solve a problem without other?s opinion. There may be different of view so the students can give different opinion. Beside that the students are also able to give real opinion orally.Keywords: Teaching Method, Improving Students? Speaking Ability, Jigsaw